2021
DOI: 10.3390/biom11081074
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Stem-like Properties: The Complex Regulation Underlying Stemness Maintenance and Cancer Development

Abstract: Embryonic stem cells (ESCs) have the extraordinary properties to indefinitely proliferate and self-renew in culture to produce different cell progeny through differentiation. This latter process recapitulates embryonic development and requires rounds of the epithelial–mesenchymal transition (EMT). EMT is characterized by the loss of the epithelial features and the acquisition of the typical phenotype of the mesenchymal cells. In pathological conditions, EMT can confer stemness or stem-like phenotypes, playing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 298 publications
(382 reference statements)
0
6
0
Order By: Relevance
“…Intriguingly, the maturity of some miRNAs bypass one or more steps in the classical pathway. These nonclassical miRNAs are similar to classical miRNAs in structure and function ( Divisato et al, 2021 ). The maturation process of nonclassical miRNAs, derived from introns, snoRNAs, endogenous short hairpin RNAs, and tRNAs, does not depend on the processing of Drosha / Dgcr8 , but only Dicer ( Abdelfattah et al, 2014 ).…”
Section: Mirnas Involved In the Osteogenic Differentiation Of Bmscsmentioning
confidence: 81%
“…Intriguingly, the maturity of some miRNAs bypass one or more steps in the classical pathway. These nonclassical miRNAs are similar to classical miRNAs in structure and function ( Divisato et al, 2021 ). The maturation process of nonclassical miRNAs, derived from introns, snoRNAs, endogenous short hairpin RNAs, and tRNAs, does not depend on the processing of Drosha / Dgcr8 , but only Dicer ( Abdelfattah et al, 2014 ).…”
Section: Mirnas Involved In the Osteogenic Differentiation Of Bmscsmentioning
confidence: 81%
“…As small single-stranded non-coding RNA molecules, miRNAs have been confirmed to exert various functions such as cell growth, apoptosis, development, differentiation and inflammation, via RNA silencing and post-transcriptional regulation of gene expression ( 19 ). An increasing number of studies have confirmed that miRNAs are essential to regulate the activities of a variety of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Divisato et al [36] recalled the evidence for the tumor-suppressing properties of miR-29 family members; in particular, miR-29a, involved in the early differentiation of stem cells, could mediate antiproliferative effects on melanoma cells by downregulating CDK6, a regulator of the G1/S phase. miR-29 has been already classified as a tumor-suppressor miRNA for different tumors, but now the possibility to use synthetic miR-29 as a therapeutic tool seems closer for the treatment of melanoma.…”
Section: Melanomamentioning
confidence: 99%